Development of an Anti-Bullying Pocket Book Cua Meci Angi Based on Local Wisdom Values of Maja Labo Dahu for Elementary School Students - A. Gafar Hidayat; Tati Haryati; Taufik, Taufik (STKIP Taman Siswa Bima, 2024)
Development of an Anti-Bullying Pocket Book